Manejo de contenidos audiovisuales para un programa de ventas de productos electrónicos y video tutorial para validación del canal de retorno en el sistema ISDB-TB de televisión digital. - Páez Cadena, Jeniffer Cristina (2014)
The present work looks for to create and to handle the television contents that go from the idea, script, the production until the final products that are the video tutorial and the video of sales of electronic products for its later one processes validation of the return channel to a database. To know more envelope this topic it is necessary to make a recount from the communication like outstanding source of the human process of exchange and answer of information, the new digital society with their changes toward the new technology and the digital television now not alone as radio station of contents but receiving, interactive that is to say chord with this world SMART. To the being a product that tries on the relationship between the communication and modern technologies the base that sustains the same one is the different studies it has more than enough Technologies of the Information and of the Communication (TIC´s) carried out by Manuel Castells and other authors that I will mention in the development of this grade work.